Análise da rentabilidade da estocagem de produtos agrícolas no Estado de Goiás - Batista Yaz , Manoel; Paniago, Euter; Aad Neto , Alexandre; Brandt, Sergio Alberto (Revista Ceres, 2025)
The objective of the present study was to determine the optimum storage periods for unprocessed rice, corn, dry season beans, wet season beans and soybeans for the State of Goiás. This information is necessary for the governamental storage facilities, Companhia Brasileira de Armazenamento — CIBRAZEM.